State-society and donor relations: The political economy of domestic resource mobilization in Nicaragua - Gloria Carrión (United Nations Research Institute for Social Development (UNRISD), 2017)
Nicaragua has undergone political, social, and economic turmoil since the 1930s. Periods of high social tension and violence (the Somoza Dictatorship, Contras War, U.S. Economic Embargo) were followed by relative peace and democratic transitions. Social conflicts and contradictions, however, have continued to emerge. These dynamics have circumscribed strategies for mobilizing financial resources. Nicaragua has largely depended on international aid to finance social development. The reconfiguration of aid governance at the global level, donor fatigue and the global economic crisis, however, have prompted a decrease in traditional ODA levels in Nicaragua and deeply impacted state-donor and state-society relations. Since the election of former President Daniel Ortega in 2007, Nicaragua has joined non-traditional aid schemes such as the Alternativa Bolivariana para los Pueblos de Nuestra América (ALBA). Similarly, the state is currently fostering the construction of a potential inter-oceanic canal and has struck a deal with HKND, a Hong Kong-based private enterprise, for its implementation. Both schemes have opened opportunities for market access, foreign direct investment, and domestic resource mobilization (DRM). Nonetheless, key governance issues (such as state-society dialogue, state-investor power balances, and democratization) pose challenges to these schemes' potential to transform Nicaragua's economy and society in equitable and sustainable terms. This paper proposes that current shifts in aid governance and access to new regional funds and revenue opportunities have compensated for a fall in aid from other donors and provided key resource availability for the Nicaraguan state, impacting positively on policy space and some development indicators. However, structural issues such as the level of social spending, poverty eradication and the empowerment of subaltern groups remain key challenges to be effectively addressed. Additionally, the lack of state transparency and accountability, meaningful social participation, and patron-client relations currently fostered through state programmes could become key obstacles to inclusive social policy-making and development in the long run.
Additional information: Prepared for the UNRISD project on Politics of Domestic Resource Mobilization
Keywords: 330